2004
DOI: 10.1359/jbmr.040130
|View full text |Cite
|
Sign up to set email alerts
|

NF1 Tumor Suppressor Protein and mRNA in Skeletal Tissues of Developing and Adult Normal Mouse and NF1-Deficient Embryos

Abstract: NF1 is a heritable disease with multiple osseous lesions. The expression of the NF1 gene was studied in embryonic and adult rodent skeleton and in NF1-deficient embryos. The NF1 gene was expressed intensely in the cartilage and the periosteum. Impaired NF1 expression may lead to inappropriate development and dynamics of bones and ultimately to the osseous manifestations of the disease.Introduction: Neurofibromatosis type 1 is caused by mutations in the NF1 gene encoding the Ras GTPase activating protein (Ras-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 35 publications
6
60
0
1
Order By: Relevance
“…Nf1 mRNA and neurofibromin are expressed in mouse bone and cartilage during development and adulthood [Kuorilehto et al, 2004a], and more specifically in mesenchymal stem cells, chondrocytes, osteoblasts [Elefteriou et al, 2006;Kolanczyk et al, 2007], and osteoclasts [Yang et al, 2006a]. This pattern of expression suggested that NF1-related skeletal defects stem in part from primary osseous defects caused by bone cellular dysfunctions related to generalized NF1 heterozygosity, and/or to NF1 loss of function in specific bone cell types.…”
Section: Mouse Models and Pathophysiology Of Nf1mentioning
confidence: 97%
“…Nf1 mRNA and neurofibromin are expressed in mouse bone and cartilage during development and adulthood [Kuorilehto et al, 2004a], and more specifically in mesenchymal stem cells, chondrocytes, osteoblasts [Elefteriou et al, 2006;Kolanczyk et al, 2007], and osteoclasts [Yang et al, 2006a]. This pattern of expression suggested that NF1-related skeletal defects stem in part from primary osseous defects caused by bone cellular dysfunctions related to generalized NF1 heterozygosity, and/or to NF1 loss of function in specific bone cell types.…”
Section: Mouse Models and Pathophysiology Of Nf1mentioning
confidence: 97%
“…The role of the Nf1 gene in skeletal development has not been well characterized, although the demonstration of Nf1 mRNA expression and its protein product, neurofibromin, in both osteoblasts and osteoclasts suggests that it may play a role in both osteogenesis and bone homeostasis 54 . Specifically, the Nf1 gene codes for the neurofibromin protein, a putative tumor suppressor protein with GTPase-activating function that appears to be involved in the down regulation of ras signal transduction 55 .…”
Section: Case Presentationmentioning
confidence: 99%
“…As it converts active Ras-GTP into inactive Ras-GDP, neurofibromin negatively regulates Ras activity 10 . Nf1 is expressed in many types of cells, including maturing chondrocytes, hypertrophic chondrocytes, osteoblasts, osteocytes, and osteoclasts 11 . Furthermore, its expression has been reported at fracture sites in a mouse model and at pseudarthrosis sites in a rat model 12 , suggesting the involvement of mutant Nf1 in the development of pseudarthrosis.…”
mentioning
confidence: 99%